Personality and Work Performance among Commercial Bank Employees in the Northern State of Malaysia - Asaari, Muhammad Hasmi Abu Hassan; Ramlee, Nurul Alhana M.; Desa, Nasina Mat (Globeedu Group, 2018)
This study aimed to associate the personality of commercial bank employees whether there is an influence on their work performance. Employees of two commercial banks in the Northern State of Malaysia were randomly selected as respondents. This study employed self-administered questionnaires in obtaining knowledge on personality by using the Big Five Factor Model and work performance. Results indicated that personality had an effect on work performance. Interestingly, commercial bank employees indicated that they love to be at work. Moreover, they also indicated that their trait of being agreeableness could be a good indicator of the top management of having obedient employees.